Liberation movements in Southern Africa : the ANC (South Africa) and ZANU (Zimbabwe) compared - Skagen, Kristin (Stellenbosch : Stellenbosch University, 2008)
Thesis MA (Political Science. International Studies))--Stellenbosch University, 2008.